The complete chloroplast genome and phylogenetic analysis of Cinnamomum daphnoides (Laurales: Lauraceae) - Yang Chen; Xiupeng Li; Minfen Yu; Bin Wei; Yan Huang; Jianhong Zhang (Mitochondrial DNA. Part B. Resources)
This study presents the complete chloroplast genome of Cinnamomum daphnoides (154,121 bp, GC 39.2%), a newly recorded species in China, revealing a typical quadripartite structure: a large single-copy region (93,688 bp, GC 37.9%), a small single-copy region (18,929 bp, GC 33.9%), and two inverted repeats (20,752 bp each, GC 44.3%). The genome harbors 126 genes (82 protein-coding, 36 tRNA, 8 rRNA). Phylogenetic analysis groups C. daphnoides with C. tamala, differing from prior studies. These findings clarify its systematic position within Cinnamomum and support its potential for coastal greening applications.